Adoption of koha software in universities in South-west, Nigeria (2016)
This article investigated the reasons for the adoption, purpose, functional modules and challenges of KOHA software in some universities in South-west Nigeria. Six universities were selected based on ownership (federal, state and private) and librarians in charge of the software were interviewed. Results revealed that KOHA was adopted because it was free and easy to use and the purpose was to improve service delivery to users. The cataloguing module was found to be the common module in the universities and the major challenges to its use were irregular power supply and inadequate technical support. For maximum benefit of using KOHA software in these libraries, alternative power supply and training for the librarians must be strongly considered.